The Suitability of French Immersion for Allophone Students in Saskatchewan: Exploring Diverse Perspectives on Language Learning and Inclusion - Davis, Stephen; Ballinger, Susan; Sarkar, Mela (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2019)
French immersion programs in Saskatchewan have traditionally served to further the goals of additive bilingualism between Canada’s two official languages, French and English. Whereas these programs have historically consisted of predominantly Anglophone populations, recent trends in immigration have contributed to the increasingly diverse linguistic backgrounds of students throughout the province. The motivation, family support, and high academic achievement of allophone students learning French as an additional language have been documented extensively in Canada (Dagenais & Jacquet, 2000; Mady, 2013, 2014, 2015). Nevertheless, allophone students often do not benefit from the same access to second language education programs as their Anglophone and Francophone peers; indeed, such learners are sometimes excluded from French immersion programs on the basis of their lack of English language proficiency (Roy, 2015). Through Likert-scale surveys and semi-structured interviews, this mixed-methods research explored the perceived suitability of French immersion for allophone students by examining the perspectives of parents and educators in several schools in Saskatoon, Saskatchewan. This study will share the triangulated findings of the research, discuss the suitability of French immersion programs for allophone students, and provide recommendations for the future of such programs in Saskatchewan.